Back to the Future: Nostalgia Increases Optimism. (November 2013) - Cheung, Wing-Yee; Wildschut, Tim; Sedikides, Constantine; Hepper, Erica G.; Arndt, Jamie; Vingerhoets, Ad J. J. M.
This research examined the proposition that nostalgia is not simply a past-oriented emotion, but its scope extends into the future, and, in particular, a positive future. We adopted a convergent validation approach, using multiple methods to assess the relation between nostalgia and optimism. Study 1 tested whether nostalgic narratives entail traces of optimism; indeed, nostalgic (compared with ordinary) narratives contained more expressions of optimism. Study 2 manipulated nostalgia through the recollection of nostalgic (vs. ordinary) events, and showed that nostalgia boosts optimism. Study 3 demonstrated that the effect of nostalgia (induced with nomothetically relevant songs) on optimism is mediated by self-esteem. Finally, Study 4 established that nostalgia (induced with idiographically relevant lyrics) fosters social connectedness, which subsequently increases self-esteem, which then boosts optimism. The nostalgic experience is inherently optimistic and paints a subjectively rosier future.